HUBUNGAN PENGETAHUAN DAN SIKAP IBU BAYI (USIA 7-11 BULAN) TENTANG ASI EKSKLUSIF DENGAN PENERAPAN ASI EKSKLUSIF DI PUSKESMAS BALOI PERMAI KOTA BATAM TAHUN 2017 - Nazriwati, Nazriwati; Anjani, Arum Dwi (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2018)
The exclusive breastfeeding is very much recommended by the World Health Organization (WHO) within the first 6 months of infants’ growth and to be continued for the next two years or more. Ironically, the mothers of the infants often do not pay attention on this issue since of their lack of knowledge about exclusive breastfeeding. Therefore, this study aims to identify the correlation of the knowledge levels and attitude of infants’ mothers, specifically 7 to 10 month newborns, about the exclusive breastfeeding and how they manage to give their infants their exclusive breast milk. In turns, researchers designed an analytic survey of cross sectional approach to examine this problem. This study took time for 3 months started from February to May 2017 at BaloiPermai Community Health Centre. The total of the population investigated was 30 respondents of 7 to 11 month newborns’ mothers using accidental sampling technique with questionnaires as the data instrument.  The data collected from the questionnaire was analyzed by Chi-Square test. For the result, it is noted that 20 mothers were well-informed respondents yet did not breastfeed their babies exclusively indicated from p value = 1.000, besides, 10 mothers possessed good level attitude, nevertheless did not breastfeed exclusively specified form p value = 1.000. From these findings, it can be drawn a line that there is no significant correlation on the level of mothers’ knowledge and attitude toward the feeding of the exclusive breastfeeding to their under 1 year old infants in BaloiPermai Community Health Centre. Finally, it is expected that all officers as well as the facilities of the Community Health Centre to be able to support the mothers in exclusive breastfeeding program in the future.